2021
DOI: 10.1111/mice.12753
|View full text |Cite
|
Sign up to set email alerts
|

Crack detection using fusion features‐based broad learning system and image processing

Abstract: Deep learning has been widely applied to vision-based structural damage detection, but its computational demand is high. To avoid this computational burden, a novel crack detection system, namely, fusion features-based broad learning system (FF-BLS), is proposed for efficient training without GPU acceleration. In FF-BLS, a convolution module with fixed weights is used to extract the fusion features of images. Feature nodes and enhancement nodes randomly generated by fusion features are used to estimate the out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(51 citation statements)
references
References 95 publications
(74 reference statements)
0
51
0
Order By: Relevance
“…Nowadays, machine learning (ML) and deep learning (DL) have been at the forefront of a plethora of research activities in many disciplines, where topics in structural engineering, for example, system parameter identification (Perez‐Ramirez et al., 2016), bolt loosening detection (Yang et al., n.d.), and crack detection, significantly benefit from these technologies. In order to reduce the cost and safety risk while improving detection accuracy and automation, researchers have proposed a variety of image detection technologies combining ML/DL with CV to recognize cracks (Kong et al., 2021; Liang, 2019; Miao et al., 2021; Żarski et al., 2021; Zhang & Yuen, 2021). In general, vision‐based crack detection has three main tasks: identification, localization, and segmentation.…”
Section: Background and Motivationsmentioning
confidence: 99%
“…Nowadays, machine learning (ML) and deep learning (DL) have been at the forefront of a plethora of research activities in many disciplines, where topics in structural engineering, for example, system parameter identification (Perez‐Ramirez et al., 2016), bolt loosening detection (Yang et al., n.d.), and crack detection, significantly benefit from these technologies. In order to reduce the cost and safety risk while improving detection accuracy and automation, researchers have proposed a variety of image detection technologies combining ML/DL with CV to recognize cracks (Kong et al., 2021; Liang, 2019; Miao et al., 2021; Żarski et al., 2021; Zhang & Yuen, 2021). In general, vision‐based crack detection has three main tasks: identification, localization, and segmentation.…”
Section: Background and Motivationsmentioning
confidence: 99%
“…They have also used over 20,000 images of 1024 × 1024 higher resolution images. Long-short term memory (LSTM) based deep learning convolutional neural networks have also been applied for crack identification [ 17 ]. This paper is unique in the sense that the use of the CNN-LSTM type method has not been presented before in literature for problems of crack identification.…”
Section: Introductionmentioning
confidence: 99%
“…With the introduction of a convolutional neural network (CNN), researchers found that this type of network based on convolution, pooling, and fully connected layers allows for automated feature extraction, and many automated damage detection methods are based on this type of network 22–24 . Zhang and Yuen 25 proposed a novel crack detection system; it is a fusion features‐based broad learning system that has the advantage of efficient training without GPU acceleration. Kim et al 26 proposed a shallow CNN‐based architecture for surface concrete crack detection, and the hyperparameters of the proposed model were optimized to achieve the maximum accuracy of crack detection with the least calculation.…”
Section: Introductionmentioning
confidence: 99%